Mobilizing curriculum studies in a (virtual) world: Open Access, edupunks, and the public good - Corrigan, Julie Ann; Ng-A-Fook, Nicholas (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
Despite societal imperatives for equity—whether espoused by nation states or transnational agencies like UNESCO—current models of higher education are unequivocally failing to provide universal access. This paper seeks to explore the (cyber)spaces (un)occupied by higher education, specifically in the area of curriculum studies, arguing that the World Wide Web can be used to effect the democratization of education. Further, it argues for the benefits of Open Access research by means of a small-scale empirical study, the results of which indicate that making research openly accessible does not diminish the impact of research, but rather may actually increase it. Keywords: Open Access, Open Education, curriculum studies, higher education, Web 2.0